238Pu, 239,240Pu, 241Am, 90Sr and 137Cs in soils around nuclear research centre Rez, near Prague - Hölgye, Z; Schlesingerová, E; Tecl, J; Filgas, R (Journal of environmental radioactivity, 2004)
Forty-four soil samples were taken around the nuclear research centre Rez, near Prague. The mean activity concentrations of 238Pu, 239,240Pu, 241Am, 90Sr and 137Cs in uncultivated soil were 0.010, 0.26, 0.12, 2.7 and 23 Bq.kg(-1), respectively. Contents of radionuclides in cultivated soil were lower and in forest soil higher than in uncultivated soil. The mean activity ratios of 238Pu/239,240Pu, 241Am/239,240Pu, 90Sr/239,240Pu and 239,240Pu/137Cs in uncultivated soil were 0.041, 0.47, 10.9 and 0.013, respectively. The mean activity ratios in cultivated and forest soils were close to the values given above. It follows from the results that the source of 239,240Pu, 90Sr and 137Cs in the studied area is deposition from atmospheric nuclear tests, in the case of 137Cs also deposition from Chernobyl accident. The contribution of the research centre effluents was not proved for these radionuclides. Increased activity ratio of 241Am/239,240Pu indicates the presence of 241Am in the soils studied emanating from sources other than nuclear tests. Uniform distribution of the 241Am/239,240Pu activity ratio around the nuclear research centre and the absence of an area with evidently higher activity ratio, including at sites lying in the main wind direction, suggest that the additional activity of 241Am does not originate from the nuclear research centre. The additional source might be the deposition following the Chernobyl accident.
Keywords: Soil Pollutants, Radioactive; monitorování životního prostředí; elektrárny; Environmental Monitoring; Radioactive Fallout; Power Plants; radioaktivní spad; Radioactive Hazard Release; stromy; Trees; Ukraine; Ukrajina; Czech Republic; radioaktivní látky znečišťující půdu; únik radioaktivních látek; Česká republika